Periglacial Processes on Heard island, Southern Indian Ocean - Kiernan, K; McConnell, A (The Royal Society of Tasmania, 2008)
Periglacial activity on Heard Island is manifested by intense physical weathering of the longest-exposed surfaces, and hillslope forms by a variety of cold-climate mass-wasting processes. Microrelief features include rudimentary sorted steps, terraces and polygons. No evidence of deep cryoturbation was obtained from excavations at 14 sites in moraines and no landforms indicative of discontinuous permafrost were identified. Periglacial landform development has been inhibited by the maritime climate and is more restricted than on other islands in the region due to the low alitude of the ice-free terrain, limited extent of glacier-free ground, and relatively recent deglaciation